1987
DOI: 10.1063/1.339018
|View full text |Cite
|
Sign up to set email alerts
|

Strain and pore pressure propagation in a water-saturated porous medium

Abstract: Articles you may be interested inMeasurement of local porosities and dielectric dispersion for a watersaturated porous medium A comparison between wave propagation in watersaturated and airsaturated porous materials A shocktube technique for studying porepressure propagation in a dry and watersaturated porous medium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…It is worth noting, however, that values of á much larger than 0´25 were used by other authors (e.g. Berryman, 1980;Van der Grinten et al, 1987) and led to a good consistency between computed and measured velocities and amplitudes of the longitudinal waves of the ®rst and second kind.Furthermore, the authors have observed the presence of a longitudinal pulse with an amplitude similar to or larger than the amplitude of the longitudinal wave of the ®rst kind (Pwave). This pulse has been considered to be the longitudinal wave of the second kind (Biot-wave).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is worth noting, however, that values of á much larger than 0´25 were used by other authors (e.g. Berryman, 1980;Van der Grinten et al, 1987) and led to a good consistency between computed and measured velocities and amplitudes of the longitudinal waves of the ®rst and second kind.Furthermore, the authors have observed the presence of a longitudinal pulse with an amplitude similar to or larger than the amplitude of the longitudinal wave of the ®rst kind (Pwave). This pulse has been considered to be the longitudinal wave of the second kind (Biot-wave).…”
mentioning
confidence: 98%
“…It is worth noting, however, that values of á much larger than 0´25 were used by other authors (e.g. Berryman, 1980;Van der Grinten et al, 1987) and led to a good consistency between computed and measured velocities and amplitudes of the longitudinal waves of the ®rst and second kind.…”
mentioning
confidence: 98%
“…The pressure trough A is not measured. It is associated with precursor tube mode 18 in the input signal p 0 (Fig. 3).…”
Section: A Borehole Fracturesmentioning
confidence: 99%
“…The frequency band width was investigated in a previous article (Chao et al 2004) and found to be between 0.5 and 80 kHz, approximately. Van der Grinten et al (1985, 1987, Sniekers et al (1989), and Smeulders and Van Dongen (1997) also performed shock-tube experiments on water-saturated and partially saturated samples, but here we focus on borehole wave along water-saturated samples.…”
Section: Introductionmentioning
confidence: 99%